EXPOSURE TRACKER LEDGER - Oliveira, Tomás Honório (2022)
On March 11, 2020, the novel coronavirus (COVID-19) was declared a global pandemic. With no treatment or vaccine available at the time, it was necessary to rely on non-pharmaceutical methods for case identification and contact tracing. This kind of approach has good results in detecting and preventing tuberculosis, sexually transmitted infections, and vaccine-preventable diseases. Contact tracing and keeping safe distances are crucial to containing the spread of COVID-19. Nonetheless, contact tracing is a complex intervention, it involves quarantining and investigating close contacts. Manual contact tracing methods are slow, require a large amount of effort, and, more often than not, rely on the memory or assumptions of individuals. To combat these downsides, contact tracing applications were developed, resulting in quicker and more reliable recognition of infected individuals. However, because of the complex nature of these applications and their lack of transparency, a large portion of the population started doubting the privacy of the data collected. On the other hand, one of the beacons of privacy we saw appear over the years was Distributed Ledgers. More accurately, the appearance of blockchain technology. By merging both contact tracing with a Distributed Ledger we hope to solve many of the issue faced by other applications. That being said, conventional Blockchain technologies, such as Bitcoin or Ethereum, cannot support a large amount of transactions in any meaningful way. At least for a use case like contact tracing, that may require the interaction of millions of users. However, Blockchain is not limited to only Bitcoin or Ethereum, and one of the most prominent projects launched in the past five years is actually Hyperledger. Hyperledger is an umbrella project focused on developing tools, frameworks, and libraries for enterprise-level blockchain implementations. Hyperledger is really interesting, but if we want to support a large amount of transaction, we have to choose which one of his underlying project is the most resilient for our use case. That’s how we got to Hyperledger Sawtooth, a project that seeks to remain distributed while offering a secure environment for Smart Contracts. Perfect for building an application focused on data privacy and transparency. With that said, the development applied throughout the project was the combination of a lot of research both regarding contact tracing, as well as regarding Hyperledger Sawtooth. Despite many challenges, the development of a contact tracing application focused on data privacy was achieved.